1995
DOI: 10.1073/pnas.92.16.7287
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic changes in developing retinal neurons result in regenerative failure of their axons.

Abstract: The failure of mature mammalian central nervous system axons to regenerate after transection is usually attributed to influences of the extraneuronal milieu.Using explant cocultures of retina and midbrain tectum from hamsters, we have found evidence that these influences account for failure of regrowth ofonly a small minority of retinal axons. For most of the axons, there is a programmed loss of ability to elongate in the central nervous system. We show that there is a precipitous decline in the ability of ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
132
0
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(140 citation statements)
references
References 31 publications
7
132
0
1
Order By: Relevance
“…Axons from P2 or older hamster retinas have lost the ability to reinnervate even embryonic tectal explants (Chen et al 1995). Purkinje cells in cerebellar slices show a similar age-related inability to re-extend axons out of cultured slices (Dusart et al 1997).…”
Section: Intrinsic Growth Ability Of Cns Neurons Is Developmentally Rmentioning
confidence: 98%
“…Axons from P2 or older hamster retinas have lost the ability to reinnervate even embryonic tectal explants (Chen et al 1995). Purkinje cells in cerebellar slices show a similar age-related inability to re-extend axons out of cultured slices (Dusart et al 1997).…”
Section: Intrinsic Growth Ability Of Cns Neurons Is Developmentally Rmentioning
confidence: 98%
“…In these two systems, identified neurons survive the axotomy caused by organotypic culture processing and are able to regenerate axonal processes in vitro and to reestablish their correct pathway and target specificity (Li et al, 1994;Chen et al, 1995;Linke et al, 1995). Moreover, the ability to regenerate is age-dependent, because the regeneration fails in cultures taken from older animals (Chen et al, 1995;Li et al, 1995). Organotypic cultures could therefore mimic the in vivo situation, and they seem particularly suitable for studying Purkinje cell survival and regeneration.…”
Section: Abstract: Axonal Regeneration; Neuronal Survival; Cerebellumentioning
confidence: 99%
“…The timing of these sequential stages reveals that the end of the developmental axonal growth and regeneration-permissive critical period coincides with the initiation of Purkinje cell efferent synaptogenesis. It can be suggested that this synaptogenesis may turn off the genetic program for axonal elongation (Tetzlaff et al, 1991;Chen et al, 1995), impairing the growth of regenerating Purkinje cell axons.…”
Section: Purkinje Cell Axonal Growth and Regeneration Is Age-dependentmentioning
confidence: 99%
“…However, besides these extrinsic in¯uences on regeneration it has become increasingly clear in the last years that intrinsic growth properties of the neurons are likely to be as important [for reviews see Fawcett (1992) and Caroni (1997)]. There is now evidence for dierences in growth potentials of various neuronal types (Rossi et al, 1995) and a decline in regenerative axonal response with neuronal age (Chen et al, 1995; 1997). While the characterization of determinants for regeneration failure is still not brought to an end, the concept emerges that axonal regeneration depends on the interplay between extrinsic cues and intrinsic properties of the lesioned neuron.…”
Section: Hypotheses To Explain Failure Of Axonal Regeneration In the mentioning
confidence: 99%